If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 77 = 90 Reorder the terms: 77 + 13x = 90 Solving 77 + 13x = 90 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-77' to each side of the equation. 77 + -77 + 13x = 90 + -77 Combine like terms: 77 + -77 = 0 0 + 13x = 90 + -77 13x = 90 + -77 Combine like terms: 90 + -77 = 13 13x = 13 Divide each side by '13'. x = 1 Simplifying x = 1
| x^2+2ix+1=0 | | f(x)=9x^2-16 | | 5x-4y=10findy | | 65+2x-5=180 | | 3x(4-8+3)= | | 24ax-(1+a^2)x^2=0 | | 2w-8y=zy | | 3.2e-08=x | | n-8+9=1-4n | | 2(x-3)=.5(4x-12) | | -11j-6+j=30 | | (3x+1/2)+(7x-41/2)= | | 2x^2+4x-5-5x^2+4x+1= | | 2X(X+4)=14 | | 13x+51=90 | | 5=6v | | f(x)=lx-1l+4 | | 5x+5=8x-13 | | -14-3n=5n-6n | | 5.61-8.94=3.76m+4.86 | | 5(w+2)=4(w+1) | | 13x+167=180 | | 6x-5x+4=-6 | | w=3(x+y+z)y | | v-16=-6 | | 3c-36=-3c-12 | | 9y-5y+10=-19 | | 0.33-4=-8 | | 2=5w+12 | | 5s-21=39 | | m=6(p+q)q | | 3(x+2)=-5-2(x-4) |